Christianity, Democracy, and the Shadow of Constantine - Demacopoulos, George E. (Orthodox Christianity and Contemporary Thought, 2016)
The collapse of communism in eastern Europe has forced traditionally Eastern Orthodox countries to consider the relationship between Christianity and liberal democracy. Contributors examine the influence of Constantinianism in both the post-communist Orthodox world and in Western political theology. Constructive theological essays feature Catholic and Protestant theologians reflecting on the relationship between Christianity and democracy, as well as Orthodox theologians reflecting on their tradition's relationship to liberal democracy. The essays explore prospects of a distinctively Christian politics in a post-communist, post-Constantinian age.